Digital Storage in Consumer Electronics The Essential Guide - Coughlin, Thomas M. (Springer International Publishing, 2018)
This book provides an introduction to digital storage for consumer electronics. It discusses the various types of digital storage, including emerging non-volatile solid-state storage technologies and their advantages and disadvantages. It discusses the best practices for selecting, integrating, and using storage devices for various applications. It explores the networking of devices into an overall organization that results in always-available home storage combined with digital storage in the cloud to create an infrastructure to support emerging consumer applications and the Internet of Things. It also looks at the role of digital storage devices in creating security and privacy in consumer products. Provides a complete guide to technical aspects of digital storage for consumer electronics; Discusses the technology of digital storage devices used in common consumer applications and shows how they are selected and integrated into a marketable product; Provides an updated, second edition to address the many changes in technology and applications that have arisen, providing critical information for designers and storage device developers.